1985
DOI: 10.1007/bf00283144
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological modifications induced in rat islets by pentamidine and other diamidines in vitro

Abstract: The antiprotozoal drug pentamidine can be toxic to islet cells in vivo and in vitro. Rat islets were exposed to pentamidine (mesylate and isethionate salts) and six other structurally related diamidines. The beta-cell response to arginine + theophylline was suppressed by pentamidine (10(-2) mmol/l) while the glucagon and somatostatin secretions persisted. All diamidines tested suppressed the beta-cell function, with a log-dose-response proportionality, the mesylate compound being more potent than pentamidine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…While this was the case with the shortest duration of therapy (9 days), the one with the longest duration (21 days) was accompanied by severe pancreatitis [14]. These clinical observations support the results of animal models in which the toxicity of pentamidine on the ß-cells of the pancreas appeared time dependent, dose dependent, and irreversible [2,3,11]. Renal insufficiency has been shown to increase toxicity, but liver damage does not seem to affect toxicity of the drug [2].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…While this was the case with the shortest duration of therapy (9 days), the one with the longest duration (21 days) was accompanied by severe pancreatitis [14]. These clinical observations support the results of animal models in which the toxicity of pentamidine on the ß-cells of the pancreas appeared time dependent, dose dependent, and irreversible [2,3,11]. Renal insufficiency has been shown to increase toxicity, but liver damage does not seem to affect toxicity of the drug [2].…”
Section: Discussionsupporting
confidence: 59%
“…Persistent IDDM following pentamidine has been reported in about 25 cases so far [3,4,7,8,10,14]. There are 12 case reports from India on patients treated for kala-azar [8].…”
Section: Discussionmentioning
confidence: 99%
“…There is a dose-dependent toxicity with a threshold total dose, which appears to be in the range of 4 to 9 gm, at which irreversible damage to the ␤-cells may occur (Perronne et al, 1990). This damage is probably similar to that seen with streptozotocin in that the cells having a high energy requirement and highly active mitochondria are more susceptible to the oxidative damage of these compounds (Boillot et al, 1985).…”
Section: G Diamidinesmentioning
confidence: 96%
“…Pentamidine induced hyperglycemia is attributed to either hyperamylasemia causing an increase in glucagon release or decreased insulin release, especially after a meal [47]. In vitro studies found that pentamidine induces irreversible β cell damage, secretory defect and necrosis precipitating the development of DM [48][49][50]. Risk factors associated with hyperglycemia include higher cumulative or single pentamidine dose and renal impairment [46].…”
Section: Pentamidinementioning
confidence: 99%